Development of an Engineering Design Process-Based Digital IPAS Module to Enhance Students' Creative Thinking - Fitriani, Novia; Sutisnawati, Astri; Uswatun, Din Azwar (Jurnal Paedagogy, 2026)
This study aims to develop an integrated IPAS digital module based on the Engineering Design Process (EDP) for the topic of light and to evaluate its feasibility and effectiveness in improving the creative thinking skills of fifth-grade elementary school students. This research employed a Research and Development (R&D) approach using the ADDIE development model. The module was developed using Canva Edu and transformed into an interactive flipbook through the Heyzine platform. The feasibility of the developed module was assessed through evaluations by practitioners, media experts, and subject matter experts using a 4-point Likert scale. The validation results indicated that the module obtained an overall average score of 92%, which was categorized as “highly feasible.” To examine its effectiveness, the creative thinking skills of the experimental group (n = 22) were compared with those of the control group (n = 33). The pretest and posttest data were analyzed using the nonparametric Mann–Whitney U test, resulting in an asymptotic significance value (2-tailed) of 0.006 (p < 0.05). This finding indicates a statistically significant difference in creative thinking skills between the two groups. The experimental group that received the EDP-based IPAS digital module achieved a higher mean score (35.25) than the control group (23.17). Therefore, the EDP-based IPAS digital module is considered highly feasible for classroom implementation and has been statistically proven to enhance fifth-grade students’ creative thinking skills in learning the concept of light.